Semicarbazide-sensitive amine oxidase & 5-HT in dental pulp - O'Sullivan, Michael (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2000)
This thesis investigated the behavior of semicarbazide sensitive amine oxidase (SSAO) and the unique activity that it possesses towards 5-hydroxytryptamine (5-HT) in various dental pulp tissues. This summary presents the findings of each chapter of this thesis.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin